Conjugated Polymer-Based Fluorescence Turn-On Sensor for Nitric Oxide - Smith, Rhett C. (2005)
[Image: see text] A turn-on fluorescent sensor for NO (g) in solution was synthesized using a bipyridyl-substituted poly(p-phenylene vinylene) derivative (CP1) as the sensory scaffold. The action of NO (g) upon the CP1–Cu(II) complex reduces it to the CP1–Cu(I) complex with a concomitant 2.8-fold increase in emission intensity. The reagent is selective for NO (g) versus other biological reactive nitrogen species, except for nitroxyl, and has a detection sensitivity limit of 6.3 nM.